The digestive and defensive basis of carcass utilization by the burying beetle and its microbiota - Heiko Vogel (Nature Portfolio, 2017)
Burying beetles feed their offspring on the carrion of vertebrate animals. Here, the authors study gene expression in the insect’s gut, as well as the composition of the microbiota in the gut and in carcasses, providing evidence for metabolic cooperation between host and specific microbes.